Desempeño laboral de las secretarias y su incidencia en los procesos administrativos del Gobierno Autónomo Descentralizado Provincial de los Ríos. - Saenz Mora, Evelia Ornella (2016)
His research work was carried out in the Autonomous Decentralized Provincial Government of the Rivers, on the work performance of the secretaries and their impact on administrative processes. In this work several processes were carried out to describe the problem that was posed. For the purpose of the investigation, a problem tree was organized in relation to the negative situation of the problem, in which they determined the causes and possible effects of this phenomenon. A large bibliographical consultation was carried out, queries were made to web pages where a substantial amount of expert information was found, and information was subsequently selected and validated with which the theoretical framework was structured. The survey was then applied to the various secretaries and users of the institution. In addition, an observation guide was used to monitor the processes that were carried out. After carrying out the processes it was possible to verify the results shown that the secretaries do not have a good job performance, that the training profiles are not adequate to perform as administrative assistants which makes it difficult to comply with administrative processes and good care To users.